Item Test Analyze of Entrepreneurship Readiness Instrument for Vocational School Students in East Java Indonesia - Hakim, Septian Rahman; Ekohariadi; Suparji; Harmanto; Wiwin, Elok (Studies in Philosophy of Science and Education, 2024)
Vocational High Schools (SMK), recognized as a solution to address unemployment in Indonesia, simultaneously face the challenge of having the highest open unemployment rate (TPT) compared to other educational levels, standing at 10.38%. Enhancing the quality of questions assessing entrepreneurial readiness is a pivotal approach in tackling this issue. Various factors contribute to students' preparedness for entrepreneurship. This study aims to identify these components by surveying 176 respondents. Employing the Entrepreneurial Readiness Test and analyzing it through Classical Test Theory (CTT) and the Rasch Analysis Model, the research revealed that entrepreneurial mental attitude, risk-taking ability, creativity, motivation, and entrepreneurial skills significantly influence students' readiness for entrepreneurship. The analysis yielded IMS (Infit mean-square) scores ranging from 0.88 to 1.17 and OMS (Outfit mean-square) values between 0.86 to 1.35, indicating a fit for all 50 items in the entrepreneurial readiness test.